Perception of Altered Smile Esthetics by Orthodontists, General Dentists, and Laypeople - Niknam, Ozra; Shahi, Shole; Narimisaei, Jale; Mousaei Emami, Mohabbat (Galen Medical Journal, 2025)
Background: Considering the significance of creation of a consonant smile arc and gap of information on the role of smile arc, gingival margin position, and the golden ratio in smile esthetics, this study assessed the perception of laypeople, general dentists, and orthodontists from altered smile esthetics. Materials and Methods: This descriptive study was conducted in 2019 with three rater groups: orthodontists (n=31), general dentists (n=49), and laypeople (n=61). A standardized frontal-view smile photograph of a female subject was digitally altered using Photoshop (version 19) to create images differing in (a) gingival margin position (four variations), (b) golden ratio (62%, 70%, and 80%), and (c) smile arc curvature (five variations). Raters, blinded to the alterations, evaluated each image’s attractiveness using a 10-point Likert scale. Due to non-normal data distribution, Kruskal–Wallis, Mann–Whitney, and Friedman tests were used for analysis (α=0.05). Results: The highest overall attractiveness ratings were given to the image with equal gingival margins for central and lateral incisors (M=7.16 ± 2.04), followed by the lateral margins 1 mm below the centrals (M=7.04 ± 2.01). Wider golden ratios (80%) were rated more attractive across all groups. Laypeople rated flat and reverse smile arcs significantly higher than general dentists and orthodontists (P<.05). No significant gender-based differences were observed in any category. Conclusion: The three rater groups had the same opinion regarding the smile attractiveness of most altered images except for the reverse smile arc, which was only favored by the laypeople.